La creatividad como estrategia metodológica para potenciar la comprensión lectora en los estudiantes de tercero y cuarto módulo de la escuela de “Primaria Popular” para personas con escolaridad inconclusa del Centro de Rehabilitación Social Loja, del barrio Los Faiques, parroquia San Sebastián, cantón y provincia de Loja, período académico 2014-2015 - Macas Castillo, Gloria Mariana (2016)
This research entitled creativity as a methodological strategy to promote reading comprehension in students of third and fourth module of the School of "Primary Popular" for people with unfinished schooling Social Rehabilitation Center of Loja, the Faiques neighborhood, parish San Sebastián, Canton and Loja Province, academic period 2014-2015., whose overall objective is to determine how creativity as a methodological strategy helps boost reading comprehension in students of third and fourth module of the School of "Primary Popular" for people with unfinished schooling Social Rehabilitation Center of Loja. The development of this research responds to the type of descriptive design (diagnosis) and pre-experimental. The methods used in their order were: understanding, inductive, deductive, scientific and synthetic, the technique applied was direct observation and the application of a survey for teachers and students, and thus obtain timely information for the development of research, the main finding was found was that the teacher does not encourage reading comprehension of students , also does not use creativity as a methodological strategy to motivate students toward an optimal development of the reading process and encourage them love and understanding texts when reading. In the research work they were involved 17 human talents; a teacher and 16 students, it is concluded that the application of the model of creativity as a methodological strategy to enhance reading comprehension of students significantly helped them to better understand the readings they perform